Uptake and release pattern of 14C in hens - SADARANGANI, S H; DOSHI, G R; CHHAPGAR, B F; KRISHNAMOORTHY, T M (The Indian Journal of Animal Sciences, 2013)
The uptake, retention and release pattern of 14C in hens has ben studied using labelled sucrose and acetate. The concentration of 14C in the yolk and protein parts of the egg builds up slowly, reaches peak values 5 days after the intake of the radioactivity and then decreases at the subsequent period. This decreasing trend of 14C indicated 2 component release pattern. The concentration of 14C in different organs of the hen after the experimental period (3 weeks) ranged from 60 to 270 pCi/g dry weight, constituting about 2% of the originally fed activity.